Pengaruh Kemampuan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Badan Perencanaan Pembangunan Daerah (Bappeda) Kota Surakarta - Purwanti, Diah Dewi; , Dra. Chuzaimah, S.E., M.M (2017)
The purpose of this study was to investigate the influence factor of employability and work environment to employees performance at BAPPEDA Surakarta. This study is a survey research with a quantitative approach. The tests performed in this study using a test instrument that studies test the validity and reliability test and also test the hypothesis that multiple linear regression, t test, F test and the coefficient of determination or R2. The data in this study are primary data obtained by distributing a questionnaire or questionnaires to respondents, where respondents here are employees of the Regional Development Planning Agency Suakarta. Samples taken in the study of 40 employees. Based on the results showed that work ability variable is ariable that has a significant influence on employee performance in BAPPEDA Surakarta. Also, results showed that there is simultaneous and significant influence between the ariables employability and work environment on employee performance, results obtained coefficient of determination or R2 of 25.4% of the variation changes the ups and downs caused by the change of employee performance variables employability and working environment, , While the remaining 74.6% were caused by other factors not analyzed in the model used in the study.